Lactic acid and biomethane production from bread waste: a techno-economic and profitability analysis using pinch technology - Mailaram, Swarnalatha; Narisetty, Vivek; Maity, Sunil K.; Gadkari, Siddharth; Thakur, Vijay Kumar; Russell, Stephen J.; Kumar, Vinod (Royal Society of Chemistry (RSC), 2023)
Lactic acid (LA) is a vital platform chemical with diverse applications, especially for biodegradable polylactic acid. Bread waste (BW) is sugar-rich waste biomass generated in large quantities in residential and commercial operations. Recently, we evaluated the potential of BW for LA production by Bacillus coagulans under non-sterile conditions. This work presents a techno-economic and profitability analysis for valorizing 100 metric tons of BW per day to alleviate environmental pollution with concurrent production of LA and biomethane. We compared two fermentation approaches: acid-neutral (Scenario I) and low pH (Scenario II). Traditional esterification with methanol, followed by hydrolysis of methyl lactate, was employed for downstream separation to obtain polymer-grade LA. High-pressure steam was generated from solid debris via anaerobic digestion to complement energy demands partly. Energy consumption was further attenuated by process integration using pinch technology, with around 15% and 11% utility cost savings for Scenario I and II, respectively. These processes were capital-intensive, with 42–46% of LA production cost stemming from direct and indirect costs. Utilities were the major cost-contributing factor (19–21%) due to energy-intensive water evaporation from dilute fermentation broth. Due to additional processing steps, capital investment and operating costs were slightly higher in Scenario I than in Scenario II. LA manufacturing cost was thus more for Scenario I ($2.07 per kg) than Scenario II ($1.82 per kg). The minimum LA selling price for Scenario I and II were $3.52 and $3.22 per kg, respectively, with five-year payback periods and 8.5% internal rates of return. LA was slightly more expensive for decentralized BW processing than the market price.